A ruptured cornual pregnancy with previous history of salpingectomy: rare case of 3rd ectopic pregnancy - Kalpana, B.; Dadhania, Bintu H.; Balamurugan, S. G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A cornual pregnancy is the most dangerous type of ectopic pregnancy since it can be misdiagnosed easily and has high mortality rate. It is diagnosed when the implantation site is at the junction between the fallopian tube and the uterus. It accounts for 2–4% of ectopic pregnancies. In a ruptured case, patient usually presents with hypovolemia and shock. For a successful outcome, early diagnosis and management are critical. A 29 years old woman, G3P0A2L0 with 8 weeks 5 days of amenorrhea conceived by IVF-ET with a history of left salpingectomy and right cornual cauterization, presented in emergency with complaints of lower abdominal pain, vomiting, burning micturition and giddiness. Per abdominal examination- soft with mild tenderness. Resuscitation started. All necessary investigations were done. Treatment started considering provisional diagnosis as septic shock following urinary tract infection (UTI). Ultrasound report showed uterus with thickened endometrium with hyperechoic irregular small gestational sac like structure in uterine cavity with hemoperitoneum in pelvis. Emergency laparotomy done considering a diagnosis of hypovolemic shock due to ruptured cornual ectopic pregnancy. Intra-operatively she was found to have hemoperitoneum with left sided ruptured cornual ectopic pregnancy. Early diagnosis is the cornerstone of cornual pregnancy before its rupture and to reduce the chances of maternal mortality. Combination of clinical features, increased serum Β-hCG, high resolution trans-vaginal ultrasonography gives the correct diagnosis in most of the cases. While doing antenatal ultrasonography in the first trimester, high index of suspicion is needed to diagnose cornual ectopic pregnancy. Conservative medical and surgical management is decided on clinical condition of the patient. Our case represents that a history of salpingectomy does not eliminate the potential of ipsilateral ectopic pregnancy.